2012
DOI: 10.1021/jp308586k
|View full text |Cite
|
Sign up to set email alerts
|

Packing Dependent Electronic Coupling in Single Poly(3-hexylthiophene) H- and J-Aggregate Nanofibers

Abstract: Nanofibers (NFs) of the prototype conjugated polymer, poly(3-hexylthiophene) (P3HT), displaying H- and J-aggregate character are studied using temperature- and pressure-dependent photoluminescence (PL) spectroscopy. Single J-aggregate NF spectra show a decrease of the 0-0/0-1 vibronic intensity ratio from ~2.0 at 300 K to ~1.3 at 4 K. Temperature-dependent PL line shape parameters (i.e., 0-0 energies and 0-0/0-1 intensity ratios) undergo an abrupt change in the range of ~110-130 K suggesting a change in NF cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
137
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(149 citation statements)
references
References 47 publications
12
137
0
Order By: Relevance
“…Either J-type intrachain delocalization along the ordered backbone could lead to charges within the same polymer chain, or charges could be generated across neighbouring backbones thanks to interchain H-aggregation. 73 Judging from previous studies with P3HT nanofibres and thin films, 73,84 the polaron yield is generally much higher in the latter case, providing evidence that aggregation of CPT in the ordered phase enhances the observed polaron generation. In line with this we have observed that, with excitation of the ordered phase at 580 nm, polaron formation is slightly favoured at higher temperature (40 1C compared to 5 1C), where the stationary absorption spectra with reduced relative 0-0 intensity suggest that the interchain H-aggregate character is enhanced.…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…Either J-type intrachain delocalization along the ordered backbone could lead to charges within the same polymer chain, or charges could be generated across neighbouring backbones thanks to interchain H-aggregation. 73 Judging from previous studies with P3HT nanofibres and thin films, 73,84 the polaron yield is generally much higher in the latter case, providing evidence that aggregation of CPT in the ordered phase enhances the observed polaron generation. In line with this we have observed that, with excitation of the ordered phase at 580 nm, polaron formation is slightly favoured at higher temperature (40 1C compared to 5 1C), where the stationary absorption spectra with reduced relative 0-0 intensity suggest that the interchain H-aggregate character is enhanced.…”
mentioning
confidence: 66%
“…It has been shown that intrachain coupling leads to J-aggregate type behaviour in the optical transitions. 10,12,73 The interchain coupling refers to the possibility of through-space delocalization across polymer chains that are aggregated or folded, and which are closely packed to allow molecular orbital overlap. This can be modelled as H-aggregate type behaviour.…”
Section: Polythiophene Photophysicsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are H-type (face-to-face) and J-type (head-to-tail) aggregates for P3HT 18,19) . While only 0-1 sideband appears in the former type due to the constraint of symmetry, the transition corresponding to 0-0 sideband is strongly allowed in the latter type.…”
Section: Resultsmentioning
confidence: 99%